Presidential Power in the Formation of Cabinet Posture after the State Ministries Law 2024 - Yuliandri; Charles Simabura; Beni Kurnia Illahi; Muhammad Ichsan Kabullah (Fakultas Hukum Universitas Gadjah Mada, 2024)
The President has the authority to determine the structure of the government under him as part of the President’s prerogative rights as regulated by Article 17 of the 1945 Constitution. Ironically, the Government and the House of Representatives insisted on changing the substance of Law No. 39 of 2008 concerning State Ministries through a swift amendment resulting in the enactment of Law No. 61 of 2024. One significant change in the new regulation is the removal of the limitation on the number of state ministries. It is necessary to examine how the constitutional mandate and the Law on State Ministries limit the president’s power in designing the cabinet posture in Indonesia. Second, what are the implications of unlimited presidential power in forming the cabinet posture from the administrative law and state finances perspective? This research uses normative juridical legal research with a descriptive nature and a prescription form. Based on the research, there are 4 (four) priority issues, first, the rise in the number of ministries will have an impact on the state budget’s ability to finance it, implications for the apparatus and infrastructure that will run government administration, further complicates the coordination function and authority between ministries, and the increasement is not in line with the government’s spirit to simplify the state institutions and regulations.